The assessment of magnesium-contained feed additive efficiency on nutrient digestibility and productivity in laying hens - O. S. Orishchuk; S. V. Tsap; R. V. Mylostyvyi; O. I. Chernenko; O. M. Chernenko (Theoretical and Applied Veterinary Medicine, 2025)
In recent years obtained data make great advance into new more effective feed additives development. The strategy for creating these additives targeting, first of all, satisfying the poultry physiological needs in biologically active substances. The practical value of the research lies in usage of a feed additive that does not contain toxic and carcinogenic properties and is absolutely safe for the laying hens. The purpose of our research was to identify the effectiveness of complex supplement in feeding laying hens. Crossbred laying hens were exposed to blended feed additive during 3 months with various 0.2%, 0.3%, and 0.4% doses. Observed results demonstrated that feed additive application increased nutrient digestion in laying hens and productivity by 5.4% in 0.2% exposed group. The most meaningful increase in egg production rate was detected in the groups exposed to 0.3% and 0.4% doses. Feed additive supplementation ameliorated the yolk content in eggs in a dose-dependent manner. One of reasonable mechanism of stimulatory effect of feed additive may relate to protection against magnesium deficiency in the stanard diet. The results of the study showed that the magnesium level has increased in the eggs of the experimental groups by 1.6% and 3.4%. Furthermore, the supplementation of the feed additive demonstrated beneficial effect on the digestibility of nutrients in the diet. All exposed to feed additive groups develop a growth of average egg weight from 5.9% to 8.2% with a dose-dependent manner. In addition, feed additive increased feed conversion coefficient that was bound with a decrease in feed consumption per 1 kg of egg weight. For instance, 2nd experimental group consumed food on 7.3 % lower then the similar indicator in the control group. Most meaningfult economic effect of feed additive supplementation was detected in 2nd experimental group in respect to egg production. Therefore, present results evidence that blended feed additive supplementation can be a promising strategy to maintain poultry farming profitability as well as could be proposed for alternative mineral sources implementation.